MINDFULNESS PRACTICE GIVES IMPACT ON STUDENT ACADEMIC PROCRASTINATION - CASE STUDY AT BUDDHIST HIGHER EDUCATION INSTITUTION - Priono Priono; Burmansah Burmansah; Wistina Seneru (Jurnal Scientia, 2023)
This study aimed to determine the influence of Mindfulness practices on academic procrastination in Buddhist Higher Education Institutions. Problems that occur in students are delaying college assignments, laziness, preferring other activities such as playing games, playing social media, and playing with friends compared to doing tasks, difficulty dividing time in doing college assignments and being stubborn about terms given. This study uses a quantitative approach with a survey method. The population in this study amounted to 148, with a sample of 108 obtained using the proportional random sampling technique. The research was conducted at Buddhist Higher Education Institutions with student respondents in semesters II to VIII of the Buddhist Higher Education Students. The results showed a significant adverse effect between mindfulness practices and student academic procrastination with a count of -7.572 and a significance value (p) of 0.000 <0.05. The results of simple regression analysis calculations show that the RSquare value is 0.351. This means that mindfulness practice affects academic procrastination by 35.1%, and other factors influence the remaining 64.9%.